2022
DOI: 10.3390/jpm12081285
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Alignment in Total Knee Arthroplasty Reduces Polyethylene Contact Pressure by Increasing the Contact Area, When Compared to Mechanical Alignment—A Finite Element Analysis

Abstract: Unrestricted Kinematic alignment (KA) in total knee arthroplasty (TKA) replicates the joint line of each patient by adjusting the cuts based on the anatomy of the patient. Mechanical alignment (MA) aims to restore a neutral mechanical axis of the leg, irrespective of the joint line orientation. The purpose of the present study was to compare contact pressure and contact areas of the polyethylene (PE) bearing surface as well as von Mises stress of the PE-tibial tray interface for MA and KA in the same patient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Other possible concerns of adding internal rotation to the femoral component include the creation of a more pronounced change in native tibiofemoral kinematics as demonstrated by a recent cadaver study by Heyse et al as well as higher quadriceps requirements as shown by Nettrour et al [13,25]. A recent inite element analysis by Klasan et al conirms the risk of using kinematic alignment in valgus knees by demonstrating an increased failure rate [19]. Another important inding is that approximately 18% of patients with neutrally aligned knees would also be at increased risk of patellofemoral maltracking by using robotic-assisted kinematic alignment due to the same reason.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible concerns of adding internal rotation to the femoral component include the creation of a more pronounced change in native tibiofemoral kinematics as demonstrated by a recent cadaver study by Heyse et al as well as higher quadriceps requirements as shown by Nettrour et al [13,25]. A recent inite element analysis by Klasan et al conirms the risk of using kinematic alignment in valgus knees by demonstrating an increased failure rate [19]. Another important inding is that approximately 18% of patients with neutrally aligned knees would also be at increased risk of patellofemoral maltracking by using robotic-assisted kinematic alignment due to the same reason.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible concerns of adding internal rotation to the femoral component include the creation of a more pronounced change in native tibiofemoral kinematics as demonstrated by a recent cadaver study by Heyse et al as well as higher quadriceps requirements as shown by Nettrour et al [13, 25]. A recent finite element analysis by Klasan et al confirms the risk of using kinematic alignment in valgus knees by demonstrating an increased failure rate [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may have contributed to such outcomes. Klasan demonstrated that KA, compared with MA, reduced polyethylene contact pressure, while Schroeder's results suggested that KA did not increase polyethylene wear [17,36]. Moreover, with the implementation of intraoperative navigation and roboticassisted systems, non-human-induced outliers have decreased, leading to enhanced precision [4,14,37,40,42].…”
Section: Discussionmentioning
confidence: 99%
“…(C) Reprinted with permission from ref. Klasan et al (2022) (Copyright 2022; MDPI, Basel, Switzerland).…”
Section: Application Of Fea In Tkamentioning
confidence: 99%
“… Kang et al (2020) studied ligament-preserving prostheses and found that KA had better mobility and even stress distribution than MA. Klasan et al (2022) established a finite element model for 10 patients with knee osteoarthritis to simulate TKA with mechanical alignment and kinematic alignment. The results showed a larger contact area and lower contact pressure on the polyethylene insert in TKA patients treated with kinematic alignment than in those treated with mechanical alignment ( Figure 1C ), but there was no significant difference in von Mises stress between the polyethylene insert and the tibia.…”
Section: Application Of Fea In Tkamentioning
confidence: 99%